2011
DOI: 10.1017/s0144686x10000905
|View full text |Cite
|
Sign up to set email alerts
|

A discourse of silence: professional carers reasoning about death and dying in nursing homes

Abstract: Nursing homes are a setting in which death and dying is common. How death and dying is articulated and the actions that take place in a nursing home constitute a discourse that guides the staff in their work. The aim of this study was to explore the discourse of death and dying in nursing homes from the perspective and understanding of the staff. The study draws on Foucault's discourse analysis. Data are from five focus-group discussions held with 28 staff of four different nursing homes in Sweden. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
5
35
0
Order By: Relevance
“…Further, this study confirmed previous research showing that nursing home staff have difficulties in facing death and dying as well as ethical and existential issues leading to them distancing themselves from death and dying (Albinsson and Strang, 2002, Casey et al, 2011, Österlind et al, 2011. A literature review (Hallberg, 2004) about older people's views on death and dying showed that older people need to narrate their thoughts of death and dying and that they had not prepared themselves for aspects concerning end-of-life care.…”
Section: Discussion Of the Findingssupporting
confidence: 85%
“…Further, this study confirmed previous research showing that nursing home staff have difficulties in facing death and dying as well as ethical and existential issues leading to them distancing themselves from death and dying (Albinsson and Strang, 2002, Casey et al, 2011, Österlind et al, 2011. A literature review (Hallberg, 2004) about older people's views on death and dying showed that older people need to narrate their thoughts of death and dying and that they had not prepared themselves for aspects concerning end-of-life care.…”
Section: Discussion Of the Findingssupporting
confidence: 85%
“…A study involving healthcare staff at nursing homes found that they expressed a fear of death. They attempted to keep death at a distance by concentrating on practical tasks, avoiding elderly patients who were dying and not becoming involved on a deeper level in the life situations of the elderly (18). In an integrative review of the research literature in the existential area related to patients receiving palliative cancer care, few intervention studies were found.…”
Section: Introductionmentioning
confidence: 99%
“…Osterlind et al argue that death and dying in LTC homes is common, yet it evokes fear and avoidance of staff. Death is surrounded by silence, and emotions are pushed into the background (Osterlind et al, 2011).…”
Section: Resultsmentioning
confidence: 99%